Inequality, economic stress, and demographic response (Explorations in Economic History, 2025)
This special issue is devoted to empirical studies on inequalities in living standard for different social groups in the past measured as their sensitivity to economic hardship, such as high food prices. The studies are similar in that they all make use of longitudinal microdata constructed from population registers and related sources that record the demographic behavior of individuals and situate it in their household and community. Such data allows not only differentiation by age and sex, but also by occupational status and household structure. They are also similar in that they all use local data on hardship, such as food prices. The special issue moves beyond the studies of living standards in preindustrial societies conducted by the EurAsia Project on Population and Family History in terms of geography, time span, and scope. Geographically, it enriches comparisons by adding sites in Estonia, Hungary, Germany, Scotland, Spain, and South Africa. Studies from these new sites improve our understanding of how different social and economic contexts influenced the lives of different social groups. This is especially the case in Eastern Europe, where the marriage age was lower and households more complex than in Western Europe. Temporally, it expands into the twentieth century, examining living standards and demographic behavior as marketization and industrialization proceeded and modern welfare programs developed.